PERTUMBUHAN DAN LAJU EKSPLOITASI IKAN TERI PEKTO (Stolephorus Waitei) DI PERAIRAN BELAWAN KOTA MEDAN SUMATERA UTARA “Growth and the rate exploitation of Anchovy Pekto (Stolephorus waitei) in the sea of Belawan , Medan, North Sumatra” - Dede Yuanda; Miswar Budi Mulya; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Anchovy Pekto is one of fish commodity that has high economic value in Medan, especially in Belawan. This type of fish is also in demand in the local market. So as fisherman of anchovies put Anchovy Pekto as a main target catch for their fishing. But, this activity has a negative impact to Anchovy Pekto population. This research was conducted in Belawan in June to August 2015, which aims to examine growth pattern, growth parameters, condition factor, and the rate of exploitation in order to provide appropriate management model for the fish resources. Primary data is total length and wet weight of 1137 samples of Anchovy pekto, whereas secondary data is the sea surface temperature data. The cohort length of fish is separated by Bhattacarya method in FISAT II software. Based on the estimation growth parameters by Von Bertalanffyin which the asymptotic length (L∞) = 7,04 cm, the growth coefficient (K) = 1,50 per year and the age at zero length (to) = -0,15 from the empiricalPauly’s method. Then the growth equation of Anchovy Pekto is Lt = 7,04 (1-e[-150(t+0,15]). The value of b obtained from the relations of weight- length Anchovy Pekto 2,975. Anchovy Pekto growth pattern is negative allometric with an equation growth W=0,007L2,975. the highest and the lowest valueof factor conditionare 0,53 and 1,86. the rate of total mortality (Z) Anchovy Pekto is 4,42 per year with natural mortality rate (M) 2,87 per year, and fishing mortality rate 1,54 per year so that the rate of exploitation is obtained with the amount 0,34 and the value of the exploitation rate does not exceed the optimum exploitation which is 0,5.Keywords: Anchovy Pekto, Long-weight, Pattern Of Growth, Factor Condition, Mortality.